4-Hydroxy-N-[3, 5-bis(trifluoromethyl)phenyl]-1, 2, 5-thiadiazole-3-carboxamide: a novel inhibitor of the canonical NF-κB cascade. Issue 9 (31st August 2017) - Pippione, Agnese C.; Federico, Antonella; Ducime, Alex; Sainas, Stefano; Boschi, Donatella; Barge, Alessandro; Lupino, Elisa; Piccinini, Marco; Kubbutat, Michael; Contreras, Jean-Marie; Morice, Christophe; Al-Karadaghi, Salam; et al.
Abstract : Compound4, derived from IMD-0354, blocks the canonical NF-κB pathway although it is inactive on the IKKβ enzyme. Abstract : The NF-κB signaling pathway is a validated oncological target. Here, we applied scaffold hopping to IMD-0354, a presumed IKKβ inhibitor, and identified 4-hydroxy- N -[3, 5-bis(trifluoromethyl)phenyl]-1, 2, 5-thiadiazole-3-carboxamide (4 ) as a nM-inhibitor of the NF-κB pathway. However, both4 and IMD-0354, being potent inhibitors of the canonical NF-κB pathway, were found to be inactive in human IKKβ enzyme assays.